Multidisciplinary Evaluation in Patients with Lung Disease Associated with Connective Tissue Disease - Wells, Athol; Devaraj, Anand; Renzoni, Elizabetta A.; Denton, Christopher P. (Seminars in Respiratory and Critical Care Medicine, 2019)
Multidisciplinary diagnosis is now viewed as the diagnostic reference standard in interstitial lung disease (ILD). This process consists of the integration of the evidence base with clinical reasoning in the formulation of a diagnosis and requires input from clinicians, radiologists, and, in selected cases, histopathologists. In ILD associated with connective tissue disease (CTD-ILD), multidisciplinary evaluation is especially helpful when CTD is suspected but cannot be diagnosed using strict criteria. In this context, the integration of systemic clinical data, serologic information, and computed tomography and biopsy findings may allow CTD-ILD to be diagnosed. However, the value of multidisciplinary evaluation in CTD-ILD is not confined to diagnosis. The frequent coexistence of pulmonary processes other than ILD, including pulmonary vascular disease, extrapulmonic restriction, and airways disease, often has a major impact on symptoms and pulmonary function tests (PFTs). In this review, we highlight the value of multidisciplinary discussion (MDD) in reconciling clinical data, PFT, and imaging data in the accurate staging of disease severity, baseline prognostic evaluation, and the identification of progression of ILD. MDD also provides a means to combine the views of respiratory physicians and rheumatologists in formulating a treatment strategy. It is often possible to reach a robust view as to whether management should be driven by systemic disease, pulmonary disease, or both. When treatment needs to be introduced or modified for both systemic and pulmonary reasons, face-to-face discussion facilities the selection of therapeutic agents that are likely to be efficacious for both systemic and pulmonary diseases.
Keywords: interstitial lung disease; connective tissue disease; multidisciplinary evaluation; diagnosis; disease severity; prognostic evaluation; disease progression